2019
DOI: 10.1016/j.asmr.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Trends in Articular Cartilage Injuries of the Knee, Analysis of the Truven Health MarketScan Commercial Claims Database from 2005-2014

Abstract: Purpose: To evaluate trends in procedures for the treatment of chondral injuries of the knee using the MarketScan database in the hope that further work can be performed to refine the indications for chondral intervention Methods: The MarketScan Research Database was searched using Current Procedure Terminology, 4th edition, codes to identify patients who underwent chondral procedures of the knee from 2005-2014. Combined procedures, including meniscal transplant or osteotomy, were also identified. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…32,33 Meniscal surgery, either through transplant or repair, has significantly increased over the past decade, even with cartilage restoration procedures. [34][35][36][37] Addressing the meniscus allows repaired cartilage to have the greatest likelihood of successful implantation and preservation of joint integrity. 38 Lee et al 39 performed meniscal allograft transplant (MAT) alone on 222 patients and found this treatment to be effective in managing patients with advanced cartilage disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Meniscal surgery, either through transplant or repair, has significantly increased over the past decade, even with cartilage restoration procedures. [34][35][36][37] Addressing the meniscus allows repaired cartilage to have the greatest likelihood of successful implantation and preservation of joint integrity. 38 Lee et al 39 performed meniscal allograft transplant (MAT) alone on 222 patients and found this treatment to be effective in managing patients with advanced cartilage disease.…”
Section: Discussionmentioning
confidence: 99%
“…32 , 33 Meniscal surgery, either through transplant or repair, has significantly increased over the past decade, even with cartilage restoration procedures. 34 , 35 , 36 , 37 Addressing the meniscus allows repaired cartilage to have the greatest likelihood of successful implantation and preservation of joint integrity. 38 Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…This database has been used for various clinical and epidemiological studies, specifically in the field of orthopedics. 14 , 15 …”
Section: Methodsmentioning
confidence: 99%
“…This database has been used for various clinical and epidemiological studies, specifically in the field of orthopedics. 14,15 The database was queried for patients who underwent either ORIF or IMN of an intertrochanteric, peritrochanteric or subtrochanteric femur fracture using the Current Procedural Terminology (CPT) codes 27244 and 27245 (Table 1). Patients were excluded based on several criteria including (1) 6-month noncontinuous preoperative enrollment (ie, patients who were not continuously enrolled in the database for the 6-month period preceding surgery), (2) 12-month noncontinuous postoperative enrollment, (3) open fracture, and (4) those aged less than 65 years.…”
Section: Data Source and Cohort Selectionmentioning
confidence: 99%
“…This specific database has been utilized for various clinical and epidemiological studies, specifically within the field of orthopedics. 13,14 We searched the database for patients who underwent surgical fixation of a pelvic ring and/or acetabular fracture by using the most used Current Procedural Terminology (CPT) codes (Table 1). Exclusion criteria regarding patient selection consisted of six months of non-continuous pre-operative enrollment (ie.…”
Section: Data Source and Cohort Selectionmentioning
confidence: 99%